INFINITE DILUTION PARTIAL MOLAR PROPERTIES OF AQUEOUS SOLUTIONS OF NONELECTROLYTES. I. EQUATIONS FOR PARTIAL MOLAR VOLUMES AT INFINITE DILUTION AND STANDARD THERMODYNAMIC FUNCTIONS OF HYDRATION OF VOLATILE NONELECTROLYTES OVER WIDE RANGES OF CONDITIONS - Plyasunov A.V.; O'Connell J.P.; Wood R.H. (My University, 2000)
A semitheoretical expression for partial molar volumes at infinite dilution of aqueous nonelectrolyte solutes has been developed employing the collection of properties from fluctuation solution theory for use over wide ranges of temperature and pressure. The form of the solution expression was suggested by a comparison of solute/solvent and solvent/solvent direct correlation function integrals (DCFI). The selection of solvent density and compressibility as model variables provides a correct description in the critical region while second virial coefficients have been used to give a rigorous expression in the low density region. The formulation has been integrated to obtain analytic expressions for thermodynamic properties of hydration at supercritical temperatures. The equation is limited to solutes for which B12 (the second cross virial coefficient between water and a solute molecule) is known or can be estimated. Regression of the three remaining parameters gives good correlations of the available experimental data. A strategy for estimating these parameters allows prediction from readily available data.